DAS181 Treatment of Severe Lower Respiratory Tract Parainfluenza Virus Infection in Immunocompromised Patients: A Phase 2 Randomized, Placebo-Controlled Study. (11th February 2021) - Chemaly, Roy F; Marty, Francisco M; Wolfe, Cameron R; Lawrence, Steven J; Dadwal, Sanjeet; Soave, Rosemary; Farthing, Jason; Hawley, Stephen; Montanez, Paul; Hwang, Jimmy; Ho, Jennifer Hui-Chun; Lewis, Stanley; et al.
Abstract: Background: There are no antiviral therapies for parainfluenza virus (PIV) infections. DAS181, a sialidase fusion protein, has demonstrated activity in in vitro and in animal models of PIV. Methods: Adult immunocompromised patients diagnosed with PIV lower respiratory tract infection (LRTI) who required oxygen supplementation were randomized 2:1 to nebulized DAS181 (4.5 mg/day) or matching placebo for up to 10 days. Randomization was stratified by need for mechanical ventilation (MV) or supplemental oxygen (SO). The primary endpoint was the proportion of patients reaching clinical stability survival (CSS) defined as returning to room air (RTRA), normalization of vital signs for at least 24 hours, and survival up to day 45 from enrollment. Results: A total of 111 patients were randomized to DAS181 (n = 74) or placebo (n = 37). CSS was achieved by 45.0% DAS181-treated patients in the SO stratum compared with 31.0% for placebo ( P = .15), whereas patients on MV had no benefit from DAS181. The proportion of patients achieving RTRA was numerically higher for SO stratum DAS181 patients (51.7%) compared with placebo (34.5%) at day 28 ( P = .17). In a post hoc analysis of solid organ transplant, hematopoietic cell transplantation within 1 year, or chemotherapy within 1 year, more SO stratum patients achieved RTRA on DAS181 (51.8%) compared with placebo (15.8%) by day 28 ( P = .012). Conclusions: The primary endpoint was not met, but post hoc analysis of the RTRA component suggests DAS181 may have clinical activity in improving oxygenation in select severely immunocompromised patients with PIV LRTI who are not on mechanical ventilation. Clinical Trials Registration. NCT01644877. Abstract : Immunocompromised adults with severe parainfluenza received nebulized DAS181 or placebo for up to 10 days. The primary endpoint was not met, but a subgroup of severely immunocompromised patients experienced a faster return to room air by day 28 ( P = .012).